Fetomaternal outcome in COVID-19 infected pregnant women: a preliminary clinical study - Shah, Parul T.; Shah, Sapana R.; Shah, Sushma R.; Yadava, Pushpa A.; Patel, Babulal S.; Chudasama, Tanmay J. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: WHO has declared COVID-19 infection a health emergency of international concern on 11th March, 2020. It is not clear whether clinical characteristics of pregnant women with COVID-19 differ from those of nonpregnant women and whether it aggravates COVID-19 symptoms and whether antiviral therapy is necessary for COVID-19 infected pregnant women. Methods: This is prospective study of 125 cases based on the compiled clinical data for pregnant women with COVID-19 between 15th April 2020 and 10th June 2020. A laboratory confirmed positive case of COVID-19 infection in pregnant women were included. Results: The most common symptoms at presentation were cough in 61.6% (77/125) and fever in 46.4% (58/125). Other reported symptoms were sore throat in 13.6% (17/125), myalgia in 10.4% (13/125) while 38.4% (48/125) were asymptomatic. There were total 97 deliveries (including 2 twins’ deliveries) among which 3 cases had IUD. Present study reported 96 live births. The incidence of missed abortion was 2.4% (3/125). The incidence of preterm birth before 37 weeks was 8.2% (8/97). Ninety-six (96.9%) of neonates were tested for SARS-CoV-2 viral nucleic acid on nasopharyngeal and pharyngeal samples and 16.67% (16/96) were resulted positive. Conclusions: At present, there is no evidence regarding the greater risk of pregnant women to succumb to COVID-19 infection and experience severe pneumonia. The risks of spontaneous abortion and preterm birth are not increased as reported in this study but shows possibility of vertical transmission when it manifests during the third trimester of pregnancy.